Struktur dan Fungsi Sosial Cerita Rakyat Legenda Kapa Si Mikin di Kabupaten Solok - Sari, Vani Yulia; Nasution, M. Ismail (Universitas Negeri Padang, 2024)
The purpose of this research is to identify the structure of the folklore legend of Kapa si Mikin and explain the social function of the folklore legend of Kapa si Mikin. This research is a qualitative research using folklore studies. Data collection was done by interview method accompanied by note-taking and recording techniques and complemented by field observation method. The source of data in this study is the folklore of the legend of Kapa si Mikin found in Kanagarian Koto Sani District X Koto Singkarak Solok Regency obtained from native speakers. The data in this study were analyzed using three stages, namely: (1) data identification stage; (2) classification stage; (3) discussion and conclusion stage of data analysis results. The results showed that the structure of the folklore of the legend of Kapa si Mikin consists of: language style in the folklore of the legend of Kapa si Mikin using the dialect of Kanagarian Koto Sani District X Koto Singkarak Solok Regency which is easily understood by the community where the owner of the story; the number of characters and characterizations is minimalist; consists of a conventional plot using three stages of storytelling namely the initial stage, middle stage and final stage; the setting in the story includes place setting, time setting and social setting; themed family stories namely the relationship between mother and child. The social functions of the folklore of the legend of Kapa si Mikin are as a means to entertain, a means to educate, a tool to pass on oral traditions, and as a means to show identity,